Caracterização dos materiais lignocelulósicos da castanha do Brasil (Bertholletia excelsa), preparação e caracterização de seus compósitos com polipropileno - Petrechen, Gustavo Pinto (2017)
This research aimed to characterize the lignocellulosic materials of the Brazil nut (Bertholletia excelsa) extraction process and to develop biocomposites incorporating these materials with homopolymer and copolymer polypropylene matrices. The study and characterization of lignocellulosic materials involved the research of the socioeconomic context and the morphological, physical, chemical, thermal and mechanical behavior characteristics. The development and characterization of biocomposites involves the beneficiation and compatibilization of the lignocellulosic fillers with polypropylene-graft-maleic anhydride, the extrusion of the biocomposites in different formulations, the injection molding of test specimens and the characterization of the resulting biocomposites in relation to general physical properties, moisture absorption, thermal behavior, mechanical behavior under tensile and flexural stress, and impact resistance behavior. The results showed that the lignocellulosic materials are composed of the pericarp of the fruit and of the seed shells, respectively with three and five distinct layers, each one with its characteristics. The biocomposites presented higher hardness, higher elastic modulus, higher tensile and flexural strength, higher moisture absorption, lower impact strength and lower rupture elongation when compared to the pure polypropylenes of the matrices. The utilization of the polypropylene copolymer matrix provided better performance in relation to the impact absorption behavior. The performance of the filler from mesocarp of the pericarp biocomposities was superior to those filled with seed shells. Compared to other biocomposites, common woods and plastics, in general, the developed biocomposites showed good performance.